“THE WAR TOOK ITS ORIGINS IN A MISTAKE”: THE THIRD WAR OF DISPOSSESSION AND RESISTANCE IN THE CAPE OF GOOD HOPE COLONY, 1799–1803 - Webb, Denver (Scientia Militaria - South African Journal of Military Studies, 2014)
The early colonial wars on the Cape Colony’s eastern borderlands and western Xhosaland, such as the 1799–1803 war, have not received as much attention from military historians as the later wars. This is unexpected since this lengthy conflict was the first time the British army fought indigenous people in southern Africa. This article revisits the 1799–1803 war, examines the surprisingly fluid and convoluted alignments of participants on either side, and analyses how the British became embroiled in a conflict for which they were unprepared and for which they had little appetite. It explores the micro narrative of why the British shifted from military action against rebellious Boers to fighting the Khoikhoi and Xhosa. It argues that in 1799, the British stumbled into war through a miscalculation – a mistake which was to have far-reaching consequences on the Cape’s eastern frontier and in western Xhosaland for over a century.